PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA BPR DI JAWA TENGAH - Mulyana, Yana (PERMANA, 2018)
People's Credit Banks, commonly abbreviated as BPRs, are one type of bank known to serve micro, small and medium entrepreneurs with locations that are generally close to where people need them. Every company, both banks and non-banks at a time (a certain period) will report all of their financial activities. From this report, it will be read how the real condition of BPR, including weaknesses and strengths possessed. This research is quantitative research. The object of this research is all Rural Credit Banks in Central Java. Data collection techniques use documentation techniques. Hypothesis testing uses classical assumption test analysis, multiple regression analysis, simultaneous test, partial test and coefficient of determination. From the results of the study it can be concluded that 1) the ratio of non-performing loans has no significant effect on BPR profit growth in Central Java, 2) the loan to deposit ratio has a significant effect on BPR profit growth in Central Java, 3) the capital adequacy ratio has a significant effect on growth BPR profits in Central Java, 4) return on assets ratio has no significant effect on BPR profit growth in Central Java, 5) ratio of operating costs to operating income has a significant effect on BPR profit growth in Central Java, and 6) ratio of non-performing loans, loans to deposit ratio, capital adequacy ratio, return on assets and operating costs to operating income simultaneously have a significant effect on BPR profit growth in Central JavaKeywords: financial ratio, profit growth, BPR